2004
DOI: 10.1111/j.1365-3164.2004.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effects of topical therapy with 0.1% tacrolimus ointment (Protopic®) on intradermal skin test reactivity in atopic dogs

Abstract: Tacrolimus ointment (TAC) is an effective treatment for atopic dermatitis in humans and dogs. The purposes of the present study were to evaluate the effect of 4 weeks of TAC on intradermal skin testing (IST), and in case of suppression, to investigate if reactivity returned to baseline by 2 or 4 weeks post treatment. Intradermal skin test was performed using saline, histamine, lipopolysaccharide (LPS, 0.4 mg mL(-1)), house dust (25 PNU mL(-1)) and house dust mite (1 : 40 000 w/v) at weeks 0, 4, 6 and 8 on nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Similarly, Ganimian and Murnane (2016) observed that there has been a remarkable increase of higher institutions of learning in developing countries. This is also corroborated by Mahajan (2016) and Warning and Duerrenberger (2018) who posits that most developing countries especially Africa are witnessing a substantial rise in higher education enrollment. Many scholars have reported that the traditional approach to teaching and learning is still the norm in many regions in the developing countries.…”
Section: Introductionmentioning
confidence: 60%
“…Similarly, Ganimian and Murnane (2016) observed that there has been a remarkable increase of higher institutions of learning in developing countries. This is also corroborated by Mahajan (2016) and Warning and Duerrenberger (2018) who posits that most developing countries especially Africa are witnessing a substantial rise in higher education enrollment. Many scholars have reported that the traditional approach to teaching and learning is still the norm in many regions in the developing countries.…”
Section: Introductionmentioning
confidence: 60%
“…In contrast, some of the late‐phase reactions to allergens were significantly reduced by tacrolimus. Late‐phase reactions took up to 4 weeks to return to pretreatment values, but by 2 weeks after discontinuation of treatment, the 4 h reaction to house dust as well as the 4 and 6 h late‐phase reactions to HDM had returned to normal …”
Section: Resultsmentioning
confidence: 99%
“…A 0.1% tacrolimus ointment (Protopic; Astellas Pharma, Northbrook, IL, USA) was applied to the lesional skin of nine house dust‐ or HDM‐sensitive dogs with AD once daily for 4 weeks . After 4 weeks of tacrolimus, immediate IDT reactions to histamine, allergens or lipopolysaccharide were not significantly different from baseline values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion severity, 1 pruritus severity, 2 intradermal test reactivity, 12 and global assessment scales, 13 are examples of ordered categorical scales used in veterinary dermatology. Many scales are used in an ad hoc manner for lack of a validated alternative.…”
Section: Introductionmentioning
confidence: 99%